Home Based Walking Exercises and Alternative Nasal Breathing Decrease Blood Pressure in Pre-Elderly People with Hypertension - Efa Nur Aini; Nian Afrian Nuari; Adhelia Harly Avia Noviantika (Jurnal Medika Nusantara, 2024)
The condition known as hypertension is brought on by the body's elevated blood pressure as a result of the heart pounding too hard. Hypertension is caused by a variety of causes, including both modifiable and unmodifiable ones. The purpose of this study is to evaluate the impact of alternate nostril breathing and walking exercise at home on the blood pressure of senior hypertension patients. A quasi-experiment with a pre-post test control group design methodology is used in the research design. Using the Total Sampling approach, 50 respondents with hypertension made up the research sample. In two weeks, the intervention was performed four times. The paired t-test results indicate that the combination of alternate nostril breathing and home-based walking exercise has an effect on blood pressure in the treatment group (both diastolic and systolic have p values = 0.000), while the control group experiences no change in blood pressure (diastolic has p values = 0.200 and systolic has p values = 0.195). The findings of the Independent T-Test demonstrated variations in blood pressure changes in both the systolic and diastolic domains between the treatment and control groups (diastolic p-value = 0.000), and systolic (p-value = 0.000). The findings of the Independent T-Test demonstrated variations in blood pressure changes in both the systolic and diastolic domains between the treatment and control groups ,diastolic (p-value = 0.000), and systolic (p-value = 0.000). Systolic and diastolic blood pressure drop as a result of an increase in endorphin chemicals and a decrease in cortisol. This calms and relaxes the body and balances the actions of the sympathetic and parasympathetic nervous systems. It is advised that individuals with pre-elderly hypertension who are able to independently implement combination therapies in an attempt to control their blood pressure. Kata kunci: Home Based Walking Exercise, Alternate Nostril Breathing, Pre-Elderly, Hypertension